Comparison of the analgesic efficacy of spray and tablet flurbiprofen for pain after soft tissue surgery - Cennet Neslihan Eroglu; Mehmet Nuri Yuksek; Sadi Elasan; Yusuf Rodi Mizrak; Busra Karaca (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this randomized clinical study was to assess the comparative efficacy of flurbiprofen in tablet and spray formulations for postoperative pain management in oral soft tissue wounds undergoing primary closure while investigating the feasibility of achieving optimal analgesia with reduced dosage and risk. Forty patients who underwent epulis fissuratum and frenulum excision for pre-prosthetic surgery were randomly assigned to receive either tablet or spray forms of flurbiprofen. The lesion dimensions were measured preoperatively, followed by excision and primary closure. The tablet group received oral tablets containing 100 mg of flurbiprofen twice daily, whereas the spray group received an oral spray containing 0.25% flurbiprofen, administered as two sprays thrice daily. Postoperative pain was assessed using the Numerical Rating Scale (NRS) until the 7th day. Lesion size, drug consumption, and rescue analgesic use were compared between the groups. There were no statistically significant differences in the lesion size between the groups. However, the mean NRS score in the spray group was significantly lower in the spray group compared to than that in the tablet group at 6th hour postoperatively (p = 0.037). Significant differences favoring the tablet group were observed in the first three doses of the drug (p = 0.001). No patients required rescue analgesics. The spray formulation of flurbiprofen demonstrated effective and safe pain relief in oral soft tissue wounds undergoing primary closure, with no reported adverse effects.